ETIKA DAN LEMBAGA ETIKA PROFESI DI KEPOLISIAN - Trianita Sweeta Hanny Marenda; Faiz Mustofa; Zahrotul Ulfa; Tajus Syarof (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Law enforcement and good public service play an important role in maintaining order and security in the country, in the context of the Republic of Indonesia the police are one of the main pillars in the security and law enforcement system. The purpose of this study aims to analyze the ethics of the police profession in enforcing the law and as a public service, this study uses a library method that takes sources from books and journals. The results of the analysis show that the ethics of the Republic of Indonesia police profession are based on principles such as justice, integrity, courage and public service. Such principles can guide police behavior in carrying out their duties, this study makes an important contribution to understanding the ethics of the police profession. By strengthening the values ​​of police professional ethics, it is hoped that law enforcement and public service can be improved, so as to create a safer, fairer and more dignified society.